Effects of Increased Water Salinity and Temperature on the Development of Rainbow Trout Fry Syndrome ( RTFS ) Caused by Flavobacterium psychrophilum - Valentina L. Donati; Niels Lorenzen; Lone Madsen (Journal of Fish Diseases, 2026)
Flavobacterium psychrophilum , the etiological agent of Rainbow Trout Fry Syndrome (RTFS) and Bacterial Coldwater Disease (BCWD), causes varying degrees of disease and mortality in salmonid aquaculture worldwide. Because its treatment relies on the use of antimicrobials, alternative interventions are of environmental and economic interest. As for other bacterial diseases, environmental factors like water parameters play a crucial role in the development of RTFS. In this study, we investigated the effect of either increased water salinity [1% (10 g L −1 )] or water temperature (18°C ± 1°C) on the development of RTFS following challenge with F. psychrophilum in rainbow trout fry under experimental conditions (either bath challenge or co‐habitation challenge). When implemented after bath challenge, the salinity treatment delayed the appearance of clinical disease, while the temperature treatment reduced the incubation time to appearance of clinical disease. Given the positive effect of increased salinity, we further assessed the effect of the salinity treatment on disease transmission when the fish were exposed to co‐habitation challenge. While intraperitoneally injected seeder fish died within 2 weeks independent of salinity, cohabitant fish kept in water with 1% salinity had a significant increase in survival (42.6%) compared to the positive controls (17.9%). Infected dead and moribund fish were confirmed positive for F. psychrophilum . Increasing water salinity thus delayed and partly prevented RTFS. In applied terms, such a delay may give time to achieve antimicrobial susceptibility test (AST) results and initiate treatment before reaching heavy mortalities in a fish batch. Further studies should evaluate the robustness of the preventive effect of this approach, its effect on the microbial communities (fish and farm environment) and whether it could be combined with other measures (e.g., phage therapy). The effect of the warm water was surprising, as F. psychrophilum infections are reported at colder temperatures.